Automatic control of Wrist Rehabilitation Therapy (Wrist-T) device for post-ischemic stroke patient - Mohd Adib, Mohd Azrul Hisham; Mat Sahat, Idris; Ahmad, Zulkifli; Mohd Hasni, Nur Hazreen; Daud, Narimah (Universiti Teknikal Malaysia Melaka, 2018)
—Since a decade, the wrist rehabilitation services in Malaysia has been operated by the physiotherapist (PT). Throughout the rehabilitative procedure, PT commonly used a conventional method which later triggered some problems related to the effectiveness of the rehab services. Timeconsuming, long-waiting time, lack of human power and all those leading to exhaustion, both for the patient and the provider. Patients could not commit to the therapy session due to logistic and domestic problems. This problem can be greatly solved with rehabilitation robot, but the current product in the market is expensive and not affordable especially for lowincome earners family. In this paper, an automatic control of wrist rehabilitation therapy; called WRist-T device has been developed. There are based on three different modes of exercises that can be carried out by the device which is the flexion/extension, radial/ulnar deviation and pronation/supination. By using this device, the patient can easily receive physiotherapy session with minor supervision from the physiotherapist at the hospital or rehabilitation centre and also can be conducted at patient home.